Dispute Resolution of Business Actors Who Have Experienced Bankruptcy Based on Consumer Protection Law - Ellen Santoso; Gunardi Lie (Syntax Idea, 1923)
Industrial growth in Indonesia creates challenges for consumers when companies go bankrupt, which often hampers the process of returning consumer rights. Legal protection regulated in the Consumer Protection Law is important for creating a healthy economy and empowering consumers. However, legal uncertainty in resolving disputes between bankrupt business actors and consumers is still a concern. Therefore, this journal aims to provide an in-depth understanding of a fair solution for both parties. The type of research method in this writing is qualitative with document type. Qualitative research is a type of research whose results are not based on statistics or other calculations. The instrument of qualitative research is the researcher himself. The results of this research are that the resolution of consumer disputes when a company goes bankrupt is based on the Consumer Protection Law, strengthening legal protection for consumers. Steps include consumer empowerment and efficient dispute resolution, both outside the courts and through court processes, with the government playing an active role in guidance and supervision. Even though the company goes bankrupt, consumers still have the right to obtain compensation according to the law, with options such as small claims claims, legal standing for consumer protection agencies, and class actions. This all aims to ensure effective consumer protection and fair law enforcement against business actors who violate their obligations